The Effect of Gold Price on Profit Achievement at PT. Pegadaian (Persero) Maros Branch, South Sulawesi - Rachmawaty Kadir; Andi Naila Quin Azisah Alisyahbana; Fajriani Azis (Fundamental and Applied Management Journal, 2023)
The purpose of this research is to determine the effect of gold prices on profit achievement at PT Pengadaian (Persero) Maros Branch, South Sulawesi. This type of research is quantitative in nature explanatory. The population is the financial statements, and the sample is the profit and loss of PT. Pegadaian Maros Branch during the period 2018 - 2022. The data analysis technique used is simple linear regression with the help of the SPSS program. The results showed that the price of gold had a positive and significant effect on the profit achievement of PT. Pegadaian (Persero) Maros Branch South Sulawesi. This means that the price of gold is able to make a significant contribution to the achievement of the profit of PT. Pegadaian (Persero) Maros Branch South Sulawesi. Given the gold price factor that greatly affects the achievement of profit, PT. Pegadaian Maros Branch Sul-Sel needs to pay attention to pricing activities that will be carried out so that consumers and potential consumers / buyers know and understand the ups and downs of gold prices in PT. Pegadaian Maros Branch so as to increase the achievement of future profits.